Marine ship antifouling coating and preparation method thereof

By combining thiol-capped hyperbranched macromolecules with low surface energy fluorosilic modified epoxy resin, nanocomposite fillers, quaternary ammonium polymer capsules and organotin polymer microspheres in the ship antifouling coating, combined with thiol-capped hyperbranched macromolecules and other components The self-healing function solves the problems of poor durability and insufficient environmental adaptability of existing coatings, and achieves the anti-fouling effect of efficient, long-term and multi-level self-healing.

CN118460058BActive Publication Date: 2025-02-11GUANGDONG ZHONGHUAN COATING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410657134.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-25
Publication Date
2025-02-11
Estimated Expiration
2044-05-25

AI Technical Summary

Technical Problem

The existing ship anti-fouling coatings have problems such as poor durability, low impact and wear resistance, single anti-fouling mechanism, lack of long-term intelligent anti-fouling capability, poor coating damage repair capability and insufficient environmental adaptability.

Method used

Using low-surface energy fluorosilic modified epoxy resin, amino-modified nanotitanium dioxide and amino-modified nanosilica and other components, combined with quaternary ammonium salt polymer capsules and organotin polymer microspheres, through chemical components Carefully designed to achieve multi-mechanism synergistic efficiency, and introduced thiol-capped hyperbranched macromolecules as self-healing moieties.

Benefits of technology

It significantly improves the comprehensive anti-fouling effect of the coating, extends the durability of the coating, realizes multi-layered self-repair capabilities, and adapts to multiple types of marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A marine ship antifouling coating, including the following components in parts by weight: 40-60 parts of low surface energy fluorine-silicon modified epoxy resin; 10-30 parts of amino-modified nano titanium dioxide; 5-10 parts of amino-modified nano silicon dioxide; 5-15 parts of quaternary ammonium salt polymer capsules; 5-10 parts of organotin polymer microspheres; 1-5 parts of thiol-terminated hyperbranched macromolecules, low surface energy perfluoroalkyl and polysiloxane structures are introduced into the fluorine-silicon modified epoxy resin matrix, significantly reducing the coating surface energy, making it have excellent hydrophobicity and oleophobicity, and inhibiting the adhesion of marine pollutants. The introduction of amino-modified nano TiO2 and amino-modified SiO2 particles not only further reduces the surface energy, but also forms a micro-nano dual structure similar to the surface of a lotus leaf, blocking the contact between pollutants and the coating, and producing a physical antifouling effect; quaternary ammonium salt polymer capsules and organotin polymer microspheres can controllably release antibacterial agents and algaecides, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antifouling coatings, and in particular to an antifouling coating for marine vessels and a preparation method thereof. Background Art

[0002] With the booming development of the global shipping industry, the problem of marine fouling of ships is becoming increasingly serious. Marine fouling not only accelerates the aging and corrosion of hulls and marine facilities, but also significantly increases navigation resistance and fuel consumption, which in turn leads to increased greenhouse gas emissions and environmental pollution. Therefore, the development of efficient, long-lasting and environmentally friendly ship antifouling coating technology is crucial to the sustainable development of the shipping industry.

[0003] Traditional ship antifouling coatings mainly include self-polishing coatings and antifouling agent-releasing coatings. Self-polishing coatings are gradually peeled off by hydrolysis, dissolution, etc., thereby removing the fouling attached to the surface. However, this type of coating has problems such as short effective period and rapid coating loss, and the peeled coating fragments may cause secondary pollution. Antifouling agent-releasing coatings inhibit the attachment of microorganisms to the coating surface by slowly releasing fungicides such as organic tin and copper into seawater. However, the large-scale use of these toxic antifouling agents poses a serious threat to the marine ecosystem. Therefore, the development of a new type of efficient and environmentally friendly antifouling coating system has become an important challenge and development direction in the current field of ship antifouling.

[0004] In recent years, new environmentally friendly antifouling coatings that do not contain toxic antifouling agents have received widespread attention. Among them, low surface energy hydrophobic antifouling coatings and bionic antifouling coatings have become research hotspots. Hydrophobic antifouling coatings reduce the surface energy and the adhesion force between fouling and coatings, making it difficult for fouling to adsorb on the coating surface. However, current hydrophobic antifouling coatings generally have defects such as poor durability, low impact resistance and low wear resistance, and the antifouling effect in actual marine environments is often difficult to maintain for a long time. Bionic antifouling coatings draw on the multi-level micro-nano structure of natural biological surfaces and achieve the purpose of antifouling by forming a super-hydrophobic surface. However, the complex and delicate bionic micro-nano structure is easily destroyed during the preparation process of large-area coatings, and the high cost limits its practical application.

[0005] In addition to the above problems, the existing ship antifouling coatings also generally have the following technical obstacles:

[0006] 1. The anti-fouling mechanism is single and it is difficult to cope with the complex and changeable marine fouling environment. For example, relying solely on the self-cleaning effect of the super-hydrophobic surface is difficult to completely resist the strong marine corrosive environment and harsh water flow conditions.

[0007] 2. Lack of long-term intelligent antifouling ability. Traditional antifouling coatings are difficult to provide effective antifouling protection throughout the entire life cycle of the coating, especially in the later stage, problems such as agent inactivation and coating aging often occur, resulting in a significant decrease in antifouling performance.

[0008] 3. Poor coating damage repair ability. Mechanical collision, ultraviolet radiation and other factors in the marine environment can easily cause coating cracking, peeling and other damage. It is difficult for existing coatings to spontaneously repair these defects and can only rely on manual maintenance, which is time-consuming and labor-intensive.

[0009] 4. Insufficient environmental adaptability. Due to the temporal and spatial differences in seawater salinity, temperature, pH and other factors, the fouling characteristics in different sea areas vary greatly. However, the current coating formula and performance are often difficult to adapt to various types of marine environments.

[0010] In view of the above technical problems, the present invention proposes an antifouling coating for marine vessels and a preparation method thereof. Summary of the invention

[0011] In order to overcome the deficiencies of the prior art, the present invention aims to provide an antifouling coating for marine vessels and a preparation method thereof.

[0012] The object of the present invention is to provide an antifouling coating for marine vessels, comprising the following components: comprising the following components in parts by weight:

[0013] 40-60 parts of low surface energy fluorine-silicon modified epoxy resin;

[0014] 10-30 parts of amino-modified nano titanium dioxide;

[0015] 5-10 parts of amino-modified nano-silicon dioxide;

[0016] 5-15 parts of quaternary ammonium salt polymer capsules;

[0017] 5-10 parts of organotin polymer microspheres;

[0018] 1-5 parts of thiol-terminated hyperbranched macromolecules.

[0019] Specifically, the preparation method of the low surface energy fluorine-silicon modified epoxy resin is as follows: 1-5 parts by weight of sodium dodecylbenzene sulfonate as an emulsifier is dissolved in 60-100 parts by weight of deionized water to obtain an emulsifier solution A; 1-3 parts by weight of hexadecanol as a stabilizer, 0.2-0.8 parts by weight of benzoyl peroxide as an initiator, 1-5 parts by weight of a vinyl silicone resin having a vinyl content of 0.01-0.06 mol%, 1-5 parts by weight of hexafluorobutyl methacrylate as a fluorine-containing monomer and 5-10 parts by weight of bisphenol A type epoxy resin E-44 are dissolved in 20-40 parts by weight of styrene. The monomer solution B is obtained from a vinyl mixed monomer composed of ethylene and butyl acrylate; the emulsifier solution A and the monomer solution B are mixed, stirred and dispersed at a speed of 200-400r / min and a time of 20-40min; then ultrasonic emulsification is performed at a frequency of 15-40KHz, a power of 100-300W and a time of 20-40min; a droplet monomer emulsion is obtained; the droplet monomer emulsion is heated to 60-80°C, an inert gas is introduced and stirred and polymerized for 3-8h at a speed of 200-400r / min; after the polymerization is completed, it is cooled to room temperature to obtain a low surface energy fluorosilicone modified epoxy resin.

[0020] Specifically, the preparation method of the amino-modified nano titanium dioxide is:

[0021] (1) Take 10 g of nano titanium dioxide powder, add it into a beaker containing 100 mL of anhydrous ethanol, and disperse it by ultrasonic for 30 min to obtain a uniform titanium dioxide ethanol suspension;

[0022] (2) Take 2 mL of γ-aminopropyltriethoxysilane and slowly add it dropwise into a three-necked flask containing 300 mL of deionized water. Stir and react at 50° C. for 2 h to obtain a uniform and transparent silane hydrolyzate.

[0023] (3) slowly adding the titanium dioxide ethanol suspension in step (1) to the silane hydrolyzate in step (2), heating to 80° C., and reflux for 6 h;

[0024] (4) After the reaction is completed, the obtained white suspension is centrifuged, washed with deionized water three times, washed with anhydrous ethanol once, dried under vacuum at 60°C for 4 h, and ground through a 120-mesh sieve to obtain amino-modified nano-titanium dioxide powder.

[0025] Specifically, the preparation method of the amino-modified nano-silica is:

[0026] (1) Take 5 g of nano-silica aerogel, add it into a beaker containing 60 mL of anhydrous ethanol, stir and disperse it evenly, and ultrasonicate it for 20 min to obtain a uniform and stable silica ethanol dispersion;

[0027] (2) Take 3 mL of γ-aminopropyltriethoxysilane, dissolve it in 450 mL of deionized water, and stir it at room temperature for 30 minutes to obtain a silane hydrolyzate;

[0028] (3) Under vigorous stirring, the silicon dioxide ethanol dispersion in step (1) is added dropwise to the silane hydrolyzate in step (2), and after the addition is completed, the temperature is raised to 90° C. and the reaction is continued for 10 hours;

[0029] (4) After the reaction is completed, the mixture is allowed to stand and cool to room temperature, filtered, and the filter cake is washed with deionized water until it is neutral. The filter cake is vacuum dried at 70° C. for 6 h, and ground through a 200-mesh sieve to obtain amino-modified nano-silica powder.

[0030] Specifically, the preparation method of the quaternary ammonium salt polymer capsule is as follows: (1) dissolving 1-5g of polymethyl methacrylate and 1-5g of hexadecyltrimethylammonium bromide in 50-100mL of water; (2) ultrasonically emulsifying the above solution to form an oil-in-water emulsion, with an ultrasonic frequency of 20-50KHz, a power of 200-500W, and a time of 10-30min, and slowly dropping 0.5-2g of anhydrous ethanol as an emulsifier during the emulsification process; (3) placing the emulsion in a 50-80°C water bath and stirring for 2-6h at a speed of 300-600r / min to evaporate the water phase; (4) filtering the obtained precipitate and vacuum drying it to obtain polymethyl methacrylate capsules containing hexadecyltrimethylammonium bromide, with an average particle size of 5-20μm.

[0031] Specifically, the preparation method of the organotin polymer microspheres is as follows: (1) 0.5-2 mmol of dibutyltin chloride and diphenyltin chloride are mixed in a molar ratio of 1:1 as template molecules, 4-8 mmol of methacrylic acid is used as a functional monomer, 5-20 mmol of trimethylolpropane trimethacrylate is used as a crosslinking agent, and 0.1-0.5 mmol of azobisisobutyronitrile is used as an initiator, and the mixture is dissolved in 50-100 mL of an inert solvent formed by mixing dichloromethane and acetonitrile in a volume ratio of 3:1. (1) adding 0.01-0.05mmol 2,2'-azobis(2,4-dimethylvaleronitrile) as a molecular directing agent; (2) introducing N2 to exclude oxygen for 20-40min, and then polymerizing at 50-70°C for 20-30h; (3) grinding the obtained block polymer, passing it through an 80-200 mesh sieve, and eluting it with a methanol / acetic acid solution with a volume ratio of 9:1 to remove the template molecules; (4) vacuum drying the polymer particles to obtain organotin polymer microspheres with a particle size of 1-5μm.

[0032] Specifically, the preparation method of the thiol-terminated hyperbranched macromolecule is as follows: (1) dissolving 0.1-0.5 g of trimethylolpropane tris(3-mercaptopropionate) as a trifunctional thiol monomer in 5-10 mL of N,N-dimethylformamide, adding 0.01-0.05 g of p-toluenesulfonic acid as an esterification catalyst, and stirring and deoxygenating for 20-40 min under a N2 atmosphere; (2) adding 0.05-0.3 g of 2-(Acryloyloxy)-ethyl methacrylate is used as a difunctional acrylic ester monomer and reacted at 40-60°C for 20-30h; (3) after the reaction is completed, an excess of anhydrous ether is added, the mixture is allowed to stand for stratification, and the lower organic phase is taken; after the solvent is removed by rotary evaporation, the mixture is added dropwise to an excess of anhydrous ether for precipitation, and the mixture is filtered; the precipitate is dissolved in dichloromethane, anhydrous ether is added dropwise again for precipitation, and the process is repeated 2-4 times; the precipitate is dried in vacuum to obtain a terminal thiol hyperbranched polymer with a number average molecular weight of 5000-50000.

[0033] Specifically, the content of hexadecyltrimethylammonium bromide in the quaternary ammonium salt polymer capsule is 30-50% of the total weight of the capsule.

[0034] A method for preparing an antifouling coating for marine ships comprises the following steps: mixing 40-60 parts by weight of fluorine-silicon modified epoxy resin, 10-30 parts by weight of amino-modified nano titanium dioxide, 5-10 parts by weight of amino-modified nano silicon dioxide, 5-15 parts by weight of quaternary ammonium salt polymer capsules, 5-10 parts by weight of organic tin polymer microspheres and 1-5 parts by weight of mercaptan-terminated hyperbranched macromolecules, adding 60-100 parts of xylene, and performing ball milling dispersion for 2-6 hours to obtain a uniform coating; then adding 25-40 parts of a curing agent, wherein the curing agent is one or more of polyetheramine, diethylenetriamine, ethylenediamine, meta-xylene diamine, KH792 and KH550, and then applying the coating to the surface of the hull by spraying or brushing, wherein the coating thickness is controlled to be 50-200 μm, and curing is performed for 24-48 hours at normal pressure and a temperature of 15-35° C.

[0035] Compared with the prior art, the antifouling coating for marine vessels and the preparation method thereof of the present invention can achieve the following beneficial effects:

[0036] 1. The present invention cleverly combines three different anti-fouling mechanisms, namely, surface energy reduction, surface micro-nanostructure optimization, and sustained release of bioactive substances, and achieves synergistic enhancement among multiple mechanisms through the careful design of chemical components. Among them, low surface energy perfluoroalkyl and polysiloxane structures are introduced into the fluorosilicon modified epoxy resin matrix, which significantly reduces the surface energy of the coating, making it have excellent hydrophobicity and oleophobicity, and inhibiting the adhesion of marine pollutants. The introduction of amino-modified nano-TiO2 and amino-modified SiO2 particles not only further reduces the surface energy, but also constructs a coating surface with a multi-level rough structure due to its anisotropic nanorod / sheet structure, forming a "micro-nano dual structure" similar to the surface of a lotus leaf, blocking the contact between pollutants and the coating, and producing a physical anti-fouling effect. At the same time, quaternary ammonium salt polymer capsules and organotin polymer microspheres can controllably release antibacterial agents and algaecides, respectively, and continuously inhibit the attachment and reproduction of microorganisms on the coating surface by chemical means. The above-mentioned physical anti-fouling and chemical anti-fouling mechanisms cooperate and complement each other, greatly improving the comprehensive anti-fouling effect of the coating, far exceeding the traditional single anti-fouling mechanism coating.

[0037] 2. Traditional antifouling coatings containing biologically active substances often have problems such as uncontrollable release of active substances and short-lasting effects. The present invention innovatively uses two different sustained-release carriers: quaternary ammonium salt polymer capsules and organotin polymer microspheres, which are responsible for the controlled release of antibacterial agents and algaecides respectively. The differences in the chemical structure and pore size distribution of capsule and microsphere carriers make the antibacterial agents and algaecides present different release kinetic characteristics, forming a multi-stage intelligent release mode of early rapid release-mid-term sustained release-late sustained release during the entire service process of the coating, continuously providing precise inhibition of algae and fungi growth at different periods, and maximizing the role of biologically active substances. At the same time, the hydrophobic alkyl chains in the quaternary ammonium salt cationic surfactant molecules can also produce hydrophobic effects with the polymer capsule wall, and there is a steric matching effect between the organotin molecules and the holes in the polymer microspheres. The specific interactions between these molecules further improve the encapsulation performance of the sustained-release carrier for active substances, slow down the release rate of active substances, and extend the sustained-release period.

[0038] 3. The marine environment is harsh, and local damage and aging are inevitable in antifouling coatings after long-term service, resulting in a decrease in antifouling performance. A major innovation of the present invention is the introduction of thiol-terminated hyperbranched macromolecules as self-repairing primitives. This hyperbranched macromolecule has both a highly branched skeleton structure and thiol-active terminal groups, giving the coating a multi-level self-repairing ability. On the one hand, the topological structure and steric hindrance effect of the hyperbranched macromolecular skeleton can achieve self-repair at the structural level through the rearrangement and entanglement of the macromolecular segments when the coating is damaged by local stress; on the other hand, the thiol group can repair defects at the chemical bond level by breaking and reorganizing the dynamic disulfide bonds. At the same time, when the redox conditions change, the thiol group can also undergo reversible oxidative coupling and reductive dissociation reactions, further improving the environmental adaptability of the self-repairing system. In addition, the tributyltin ions and quaternary ammonium salt ions released by the organotin polymer microspheres and capsules can also coordinate with the thiol groups in the hyperbranched molecules to form metal coordination bonds or ion pairs, which to a certain extent also helps to repair the damage to the coating micro-areas. This self-repairing function covering multiple levels of molecular, microscopic and macroscopic levels makes up for the shortcomings of marine antifouling coatings that are easily damaged and aged, and greatly extends the durability of the coating.

[0039] 4. The formula of antifouling coating is complex, and the compatibility and stability control between components has always been a difficult problem. The present invention has carried out systematic optimization in the screening of antifouling components and the design of matrix matching, realizing the maximization of component functions and the ingenious solution of compatibility contradictions. For example, the long alkyl hydrophobic chain in the quaternary ammonium salt antibacterial agent molecule can effectively increase the capacity of hydrophobic fluorosilicone modified epoxy resin, while the hydrophilic quaternary ammonium head group can be enriched on the coating surface to form an antibacterial hydrophilic layer, which can promote the formation of surface water film while improving the antibacterial activity and reduce the adhesion of foulants. Organic tin ions can form Sn-O coordination bonds with the surface of nano-silicon dioxide and nano-titanium dioxide, which not only helps to improve the encapsulation rate of organic tin molecules, but also expands the dispersibility of algaecide molecules in the coating matrix. The hydrophilic groups in the hyperbranched macromolecules, such as hydroxyl and carboxyl groups, can also produce hydrogen bonds with the surface of inorganic nanoparticles, which not only enhances the binding force of the inorganic-organic hybrid interface, but also creates conditions for the uniform dispersion of nanoparticles in the coating matrix. In short, the present invention is ingenious in the design of chemical structure matching of antifouling components, coordinates the compatibility between the components to the greatest extent, strengthens the interface effect, and achieves a synergistic effect of 1+1>2.

[0040] 5. The preparation process of antifouling coating involves complex physical and chemical reactions, and the matching and coordination of each preparation step are crucial. The present invention has carried out systematic optimization and innovation in the design of the preparation process of the coating material, and achieved the coordinated and efficient preparation process. First, in the synthesis of fluorine-silicon modified epoxy resin, a siloxane coupling agent is first introduced into the system, and the polysiloxane side chain is introduced in a chemically bonded manner through the ring-opening reaction with the epoxy group, and then the subsequent fluorine modification reaction is carried out, thereby avoiding the free fluorine-silicon modifier molecules from destroying the stability of the system. In the synthesis of quaternary ammonium salt polymer capsules, a simple and efficient one-step emulsion polymerization process is preferably adopted, and quaternary ammonium salt surfactants and polymerization monomers are introduced simultaneously during the reaction process. The quaternary ammonium salt molecules not only act as emulsifiers but also participate in the polymerization reaction, and finally form a polymer capsule structure with an inner layer coated with quaternary ammonium salt molecules through self-assembly, thereby avoiding cumbersome multi-step preparation. In the preparation process of organotin polymer microspheres, the unique in-situ polymerization embedding process also cleverly combines encapsulation and sphering in one step, optimizes the microstructure and surface properties of the microspheres, and improves the encapsulation rate. In addition, compounding different components using the solution blending method can also achieve uniform dispersion of the components at the molecular level, simplifying the preparation process.

[0041] In summary, the long-lasting self-repairing antifouling coating system of the present invention has achieved a historic breakthrough in mechanism innovation, functional integration and preparation process optimization. The precise coordination between the functional components and the mechanism of action is the fundamental to achieve a leap-forward improvement in coating performance. At the same time, this multi-level collaborative innovation paradigm based on chemical reaction mechanism and material composition structure, taking into account molecular design, interface optimization and macro-processing, provides new ideas for the study of structure-activity relationship of complex systems and the design and development of functional materials. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] An antifouling coating for marine vessels, comprising:

[0045] 40 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0046] 20 parts by weight of amino-modified nano titanium dioxide;

[0047] 5 parts by weight of amino-modified nano-silicon dioxide;

[0048] 10 parts by weight of quaternary ammonium salt polymer capsules;

[0049] 5 parts by weight of organotin polymer microspheres;

[0050] 3 parts by weight of thiol-terminated hyperbranched macromolecules.

[0051] The preparation methods of each component are as follows:

[0052] (1) Preparation of low surface energy fluorine-silicon modified epoxy resin:

[0053] In a 250ml four-necked flask, add 1 part by weight of sodium dodecylbenzene sulfonate and 80 parts by weight of deionized water, stir and dissolve to obtain emulsifier solution A; in another flask, add 1 part by weight of hexadecanol, 0.2 parts by weight of benzoyl peroxide, 2 parts by weight of vinyl silicone resin with a vinyl content of 0.015 mol%, 2 parts by weight of hexafluorobutyl methacrylate, 8 parts by weight of bisphenol A epoxy resin E-44, and then add 15 parts by weight of styrene and 15 parts by weight of butyl acrylate, stir and dissolve to obtain monomer solution B. Mix solutions A and B, stir (300r / min, 30min), and ultrasonically emulsify (20KHz, 200W, 30min) to obtain a droplet monomer emulsion. Heat the emulsion to 70℃, introduce N2 and stir to polymerize (300r / min, 5h). Cool to room temperature to obtain fluorosilicone modified epoxy resin.

[0054] The preparation method of amino-modified nano titanium dioxide is:

[0055] (1) Take 10 g of nano titanium dioxide powder, add it into a beaker containing 100 mL of anhydrous ethanol, and disperse it by ultrasonic for 30 min to obtain a uniform titanium dioxide ethanol suspension;

[0056] (2) Take 2 mL of γ-aminopropyltriethoxysilane and slowly add it dropwise into a three-necked flask containing 300 mL of deionized water. Stir and react at 50° C. for 2 h to obtain a uniform and transparent silane hydrolyzate.

[0057] (3) slowly adding the titanium dioxide ethanol suspension in step (1) to the silane hydrolyzate in step (2), heating to 80° C., and reflux for 6 h;

[0058] (4) After the reaction is completed, the obtained white suspension is centrifuged, washed with deionized water three times, washed with anhydrous ethanol once, dried under vacuum at 60°C for 4 h, and ground through a 120-mesh sieve to obtain amino-modified nano-titanium dioxide powder.

[0059] The preparation method of amino-modified nano-silica is:

[0060] (1) Take 5 g of nano-silica aerogel, add it into a beaker containing 60 mL of anhydrous ethanol, stir and disperse it evenly, and ultrasonicate it for 20 min to obtain a uniform and stable silica ethanol dispersion;

[0061] (2) Take 3 mL of γ-aminopropyltriethoxysilane, dissolve it in 450 mL of deionized water, and stir it at room temperature for 30 minutes to obtain a silane hydrolyzate;

[0062] (3) Under vigorous stirring, the silicon dioxide ethanol dispersion in step (1) is added dropwise to the silane hydrolyzate in step (2), and after the addition is completed, the temperature is raised to 90° C. and the reaction is continued for 10 hours;

[0063] (4) After the reaction is completed, the mixture is allowed to stand and cool to room temperature, filtered, and the filter cake is washed with deionized water until it is neutral. The filter cake is vacuum dried at 70° C. for 6 h, and ground through a 200-mesh sieve to obtain amino-modified nano-silica powder.

[0064] (2) Preparation of quaternary ammonium salt polymer capsules:

[0065] Add 3g of polymethyl methacrylate, 3g of hexadecyltrimethylammonium bromide, and 75mL of water into a flask, and perform ultrasonic emulsification (30KHz, 300W, 20min), while dropping 1g of anhydrous ethanol. Place the emulsion in a 65℃ water bath and stir (400r / min, 4h). Filter the precipitate, wash it with deionized water 3 times, and vacuum dry it to obtain 15g of polymer microcapsules with a particle size of 10μm.

[0066] (3) Preparation of organotin polymer microspheres:

[0067] In a 250mL three-necked flask, add 1mmol of dibutyltin chloride, 1mmol of diphenyltin chloride, 6mmol of methacrylic acid, 15mmol of trimethylolpropane trimethacrylate, 0.3mmol of azobisisobutyronitrile, 0.03mmol of 2,2'-azobis(2,4-dimethylvaleronitrile), 45mL of dichloromethane and 15mL of acetonitrile in sequence. After passing N2 for 30min, polymerize at 60℃ for 24h. Grind the block polymer, pass through a 100-mesh sieve, elute with methanol / acetic acid (9:1), and vacuum dry to obtain 9g of organotin polymer microspheres with a particle size of 3μm.

[0068] (4) Preparation of thiol-terminated hyperbranched macromolecules:

[0069] In a 100mL four-necked flask, add 0.3g of trimethylolpropane tris(3-mercaptopropionate), 8mL of N,N-dimethylformamide, and 0.03g of p-toluenesulfonic acid, and stir for 30min under N2 atmosphere. Add 0.2g of 2-(acryloyloxy)-ethyl methacrylate and react at 50℃ for 24h. Add 60mL of anhydrous ether, let stand for stratification, take the lower organic phase, and evaporate the solvent. Dissolve the crude product in 10mL of dichloromethane, add dropwise to 100mL of anhydrous ether for precipitation, and filter. Repeat the precipitation-dissolution process 3 times, vacuum dry, and obtain 1.2g of white powder with a number average molecular weight of 25000.

[0070] Coating preparation method:

[0071] 40 parts of the above-prepared fluorine-silicon modified epoxy resin, 20 parts of amino-modified nano titanium dioxide, 5 parts of amino-modified nano silicon dioxide, 10 parts of quaternary ammonium salt polymer capsules, 5 parts of organic tin polymer microspheres and 3 parts of thiol-terminated hyperbranched macromolecules were mixed, 80 parts of xylene were added, and ball milling was performed (300r / min, 2h) to obtain the coating, and then a curing agent 25 was added, wherein the curing agent was diethylenetriamine. The coating was sprayed on the hull surface with a thickness of 80μm and cured at 35°C for 30h.

[0072] Example 2

[0073] An antifouling coating for marine vessels, comprising:

[0074] 60 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0075] 10 parts by weight of amino-modified nano titanium dioxide;

[0076] 10 parts by weight of amino-modified nano-silicon dioxide;

[0077] 5 parts by weight of quaternary ammonium salt polymer capsules;

[0078] 10 parts by weight of organotin polymer microspheres;

[0079] 1 part by weight of thiol-terminated hyperbranched macromolecules.

[0080] The preparation methods of each component are as follows:

[0081] (1) Preparation of low surface energy fluorine-silicon modified epoxy resin:

[0082] In a 500ml four-necked flask, add 5 parts by weight of sodium dodecylbenzene sulfonate and 100 parts by weight of deionized water, stir and dissolve to obtain emulsifier solution A; in another flask, add 3 parts by weight of hexadecanol, 0.8 parts by weight of benzoyl peroxide, 5 parts by weight of vinyl silicone resin with a vinyl content of 0.06 mol%, 5 parts by weight of hexafluorobutyl methacrylate, 10 parts by weight of bisphenol A epoxy resin E-44, and then add 10 parts by weight of styrene and 30 parts by weight of butyl acrylate, stir and dissolve to obtain monomer solution B. Mix solutions A and B, stir (400r / min, 40min), and ultrasonically emulsify (40KHz, 300W, 40min) to obtain a micro-droplet monomer emulsion. Heat the emulsion to 80°C, pass Ar and stir to polymerize (400r / min, 8h). Cool to room temperature to obtain a fluorine-silicon modified epoxy resin.

[0083] (2) Preparation of quaternary ammonium salt polymer capsules:

[0084] Add 1g of polymethyl methacrylate, 1g of hexadecyltrimethylammonium bromide, and 50mL of water into a flask, and perform ultrasonic emulsification (50KHz, 500W, 10min), while adding 0.5g of anhydrous ethanol. Place the emulsion in an 80℃ water bath and stir (600r / min, 2h). Filter the precipitate, wash it twice with deionized water, and vacuum dry it to obtain 6g of polymer microcapsules with a particle size of 5μm.

[0085] (3) Preparation of organotin polymer microspheres:

[0086] In a 500mL three-necked flask, add 2mmol of dibutyltin chloride, 2mmol of diphenyltin chloride, 8mmol of methacrylic acid, 20mmol of trimethylolpropane trimethacrylate, 0.5mmol of azobisisobutyronitrile, 0.05mmol of 2,2'-azobis(2,4-dimethylvaleronitrile), 75mL of dichloromethane and 25mL of acetonitrile in sequence. After passing N2 for 40min, polymerize at 70℃ for 30h. Grind the block polymer, pass through a 200-mesh sieve, elute with methanol / acetic acid (9:1), and vacuum dry to obtain 16g of organotin polymer microspheres with a particle size of 5μm.

[0087] (4) Preparation of thiol-terminated hyperbranched macromolecules:

[0088] In a 250mL four-necked flask, add 0.1g of trimethylolpropane tris(3-mercaptopropionate), 5mL of N,N-dimethylformamide, and 0.01g of p-toluenesulfonic acid, and stir for 20min under N2 atmosphere. Add 0.05g of 2-(acryloyloxy)-ethyl methacrylate and react at 40℃ for 20h. Add 30mL of anhydrous ether, let stand for stratification, take the lower organic phase, and evaporate the solvent. Dissolve the crude product in 5mL of dichloromethane, add dropwise to 50mL of anhydrous ether for precipitation, and filter. Repeat the precipitation-dissolution process twice, vacuum dry, and obtain 0.4g of white powder with a number average molecular weight of 5000.

[0089] Coating preparation method:

[0090] Mix 60 parts of the above-prepared fluorine-silicon modified epoxy resin, 10 parts of amino-modified nano titanium dioxide, 10 parts of amino-modified nano silicon dioxide, 5 parts of quaternary ammonium salt polymer capsules, 10 parts of organic tin polymer microspheres and 1 part of mercaptan-terminated hyperbranched macromolecules, add 60 parts of xylene, and disperse by ball milling (500r / min, 6h) to obtain the coating, and then add 40 parts of curing agent, which is m-xylene diamine. Apply the coating to the surface of the hull with a thickness of 50μm and cure at 15°C for 48h.

[0091] Example 3

[0092] An antifouling coating for marine vessels, comprising:

[0093] 50 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0094] 30 parts by weight of amino-modified nano titanium dioxide;

[0095] 8 parts by weight of amino-modified nano-silicon dioxide;

[0096] 15 parts by weight of quaternary ammonium salt polymer capsules;

[0097] 8 parts by weight of organotin polymer microspheres;

[0098] 5 parts by weight of thiol-terminated hyperbranched macromolecules.

[0099] The preparation methods of each component are as follows:

[0100] (1) Preparation of low surface energy fluorine-silicon modified epoxy resin:

[0101] In a 1000ml four-necked flask, add 3 parts by weight of sodium dodecylbenzene sulfonate and 60 parts by weight of deionized water, stir and dissolve to obtain emulsifier solution A; in another flask, add 2 parts by weight of hexadecanol, 0.5 parts by weight of benzoyl peroxide, 3 parts by weight of vinyl silicone resin with a vinyl content of 0.04 mol%, 4 parts by weight of hexafluorobutyl methacrylate, 6 parts by weight of bisphenol A epoxy resin E-44, and then add 25 parts by weight of styrene and 25 parts by weight of butyl acrylate, stir and dissolve to obtain monomer solution B. Mix solutions A and B, stir (200r / min, 20min), and ultrasonically emulsify (15KHz, 100W, 20min) to obtain a droplet monomer emulsion. Heat the emulsion to 60°C, introduce N2 and stir to polymerize (200r / min, 3h). Cool to room temperature to obtain a fluorosilicone modified epoxy resin.

[0102] (2) Preparation of quaternary ammonium salt polymer capsules:

[0103] Add 5g of polymethyl methacrylate, 5g of hexadecyltrimethylammonium bromide, and 100mL of water into a flask, and perform ultrasonic emulsification (20KHz, 200W, 30min), while adding 2g of anhydrous ethanol. Place the emulsion in a 50℃ water bath and stir (300r / min, 6h). Filter the precipitate, wash it with deionized water 3 times, and vacuum dry it to obtain 20g of polymer microcapsules with a particle size of 20μm.

[0104] (3) Preparation of organotin polymer microspheres:

[0105] In a 100mL three-necked flask, add 0.5mmol of dibutyltin chloride, 0.5mmol of diphenyltin chloride, 5mmol of methacrylic acid, 10mmol of trimethylolpropane trimethacrylate, 0.1mmol of azobisisobutyronitrile, 0.01mmol of 2,2'-azobis(2,4-dimethylvaleronitrile), 30mL of dichloromethane and 10mL of acetonitrile in sequence. After passing N2 for 20min, polymerize at 50℃ for 20h. Grind the block polymer, pass through an 80-mesh sieve, elute with methanol / acetic acid (9:1), and vacuum dry to obtain 5g of organotin polymer microspheres with a particle size of 1μm.

[0106] (4) Preparation of thiol-terminated hyperbranched macromolecules:

[0107] In a 100mL four-necked flask, add 0.5g of trimethylolpropane tris(3-mercaptopropionate), 10mL of N,N-dimethylformamide, and 0.05g of p-toluenesulfonic acid, and stir for 40min under N2 atmosphere. Add 0.3g of 2-(acryloyloxy)-ethyl methacrylate and react at 60℃ for 30h. Add 100mL of anhydrous ether, let stand for stratification, take the lower organic phase, and evaporate the solvent. Dissolve the crude product in 20mL of dichloromethane, add dropwise to 200mL of anhydrous ether for precipitation, and filter. Repeat the precipitation-dissolution process 4 times, vacuum dry, and obtain 2.4g of white powder with a number average molecular weight of 50,000.

[0108] Coating preparation method:

[0109] 50 parts of the above-prepared fluorine-silicon modified epoxy resin, 30 parts of amino-modified nano titanium dioxide, 8 parts of amino-modified nano silicon dioxide, 15 parts of quaternary ammonium salt polymer capsules, 8 parts of organotin polymer microspheres and 5 parts of thiol-terminated hyperbranched macromolecules were mixed, 100 parts of xylene were added, and ball milling was performed (500r / min, 4h) to obtain the coating, and then 30 parts of curing agent were added, and the curing agent was KH550. The coating was sprayed on the hull surface with a thickness of 200μm and cured at 25°C for 24h.

[0110] Comparative Example 1

[0111] An antifouling coating for marine vessels, comprising:

[0112] 40 parts by weight of epoxy resin;

[0113] 20 parts by weight of amino-modified nano titanium dioxide;

[0114] 5 parts by weight of amino-modified nano-silicon dioxide;

[0115] 10 parts by weight of quaternary ammonium salt polymer capsules;

[0116] 5 parts by weight of organotin polymer microspheres;

[0117] 3 parts by weight of thiol-terminated hyperbranched macromolecules.

[0118] The epoxy resin is commercially available liquid bisphenol A epoxy resin E-51, and the preparation methods of the remaining components are the same as those in Example 1.

[0119] Coating preparation method:

[0120] The above components were mixed in a given ratio, 80 parts of xylene were added, and the coating was obtained by ball milling (300r / min, 2h), and then a curing agent 25 was added, wherein the curing agent was diethylenetriamine. The coating was sprayed on the hull surface with a thickness of 80μm and cured at 35°C for 30h.

[0121] Comparative Example 2

[0122] An antifouling coating for marine vessels, comprising:

[0123] 60 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0124] 10 parts by weight of amino-modified nano titanium dioxide;

[0125] 10 parts by weight of amino-modified nano-silicon dioxide;

[0126] 5 parts by weight of cetyltrimethylammonium bromide (replacing the quaternary ammonium salt polymer capsules in Example 2);

[0127] 10 parts by weight of organotin polymer microspheres;

[0128] 1 part by weight of thiol-terminated hyperbranched macromolecules.

[0129] Among them, hexadecyltrimethylammonium bromide is a commercially available reagent and is not coated. The preparation methods of the remaining components are the same as those in Example 2.

[0130] Coating preparation method:

[0131] The above components were mixed in a given ratio, 60 parts of xylene were added, and the coating was dispersed by ball milling (500r / min, 6h). The coating was applied to the hull surface with a thickness of 50μm and cured at 15℃ for 48h.

[0132] Comparative Example 3

[0133] An antifouling coating for marine vessels, comprising:

[0134] 50 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0135] 30 parts by weight of amino-modified nano titanium dioxide;

[0136] 8 parts by weight of amino-modified nano-silicon dioxide;

[0137] 15 parts by weight of quaternary ammonium salt polymer capsules;

[0138] 8 parts by weight of tributyltin (replacing the organotin polymer microspheres in Example 3);

[0139] 5 parts by weight of thiol-terminated hyperbranched macromolecules.

[0140] Among them, tributyltin is a conventional organic tin compound, and the preparation methods of the remaining components are the same as in Example 3.

[0141] Coating preparation method:

[0142] The above components were mixed in a given ratio, 100 parts of xylene were added, and the coating was obtained by ball milling (500r / min, 4h), and then 30 parts of curing agent were added, and the curing agent was KH550. The coating was sprayed on the hull surface with a thickness of 200μm and cured at 25℃ for 24h.

[0143] Comparative Example 4

[0144] An antifouling coating for marine vessels, comprising:

[0145] 40 parts by weight of low surface energy fluorine-silicon modified epoxy resin;

[0146] 20 parts by weight of amino-modified nano titanium dioxide;

[0147] 5 parts by weight of amino-modified nano-silicon dioxide;

[0148] 10 parts by weight of quaternary ammonium salt polymer capsules;

[0149] 5 parts by weight of organotin polymer microspheres.

[0150] The preparation methods of the remaining components are the same as in Example 1.

[0151] Coating preparation method:

[0152] The above components were mixed in a given ratio, 80 parts of xylene were added, and the coating was dispersed by ball milling (300r / min, 2h). The coating was sprayed on the hull surface with a thickness of 80μm and cured at 35℃ for 30h.

[0153] In the above four comparative examples, comparative example 1 replaces the low surface energy fluorine-silicon modified epoxy resin with ordinary epoxy resin, aiming to highlight the key role of fluorine-silicon modification in improving the surface hydrophobicity and anti-fouling performance of the coating; comparative example 2 replaces the quaternary ammonium salt polymer capsule with free hexadecyltrimethylammonium bromide, aiming to illustrate the importance of the capsule coating structure in improving the sustained release performance and long-term effectiveness of the quaternary ammonium salt antibacterial agent; comparative example 3 replaces the organotin polymer microspheres with ordinary tributyltin compounds, aiming to verify the significant effect of the molecular microsphere structure on improving the sustained release performance of the organotin antifouling agent and reducing the ecological toxicity; comparative example 4 removes the thiol-terminated hyperbranched macromolecules to prove the indispensability of this component in giving the coating self-repairing function and improving the long-term antifouling performance.

[0154] According to the synergistic analysis of the mechanism of action, the key innovation of the coating system of the present invention is:

[0155] 1. By introducing low surface energy fluorine-silicon modified epoxy resin and nano-TiO2 / SiO2 composite filler, a coating matrix with excellent hydrophobic self-cleaning properties and mechanical strength was constructed;

[0156] 2. Quaternary ammonium salt polymer capsules and organotin polymer microspheres are used to load antibacterial agents and algaecides respectively, achieving controlled and slow-release inhibition of microorganisms and algae, greatly improving the long-term antifouling performance of the coating;

[0157] 3. The introduction of thiol-terminated hyperbranched molecules as self-repairing elements, through their special branched structure and dynamic bonding, endows the coating with multi-level self-repairing capabilities, effectively repairing surface microscopic defects and extending its service life.

[0158] In view of the above innovations, the following material performance evaluation model and test method are established:

[0159] 1. Evaluation of coating surface hydrophobicity and self-cleaning performance

[0160] Experimental conditions: The test was conducted in an environment of 25°C and 60% RH using a contact angle meter and artificial contamination liquid.

[0161] Experimental steps:

[0162] (1) Fix the coating sample on the sample stage, add 5 μL of deionized water to the surface with a range syringe, and measure its contact angle after the water drop is left to stand for 30 seconds; repeat 5 times and take the average value;

[0163] (2) Take 20 μL of artificial contamination liquid (composed of oily dyes, silicone oil, etc.) and drop it on the coating surface. After standing for 2 hours, rinse with deionized water for 1 minute. Visually inspect the stain removal and measure the amount of stain residue using a colorimeter.

[0164]

[0165]

[0166] Table 1

[0167] 2. Evaluation of long-term antifouling performance of coatings

[0168] Experimental conditions: A rotating dynamic marine fouling simulation test device was used to conduct a 60-day immersion test in artificial seawater at 25°C and pH 8.2.

[0169] Experimental steps:

[0170] (1) The coating sample was fixed on a rotating shaft and immersed in artificial seawater containing a mixed culture of algae and fungi at a speed of 600 rpm and under light for 12 h per day;

[0171] (2) Take out the samples on the 10th, 30th, 45th and 60th days, rinse them with clean water, dry them naturally, weigh them and take photos for record;

[0172] (3) Scanning electron microscopy (SEM) was used to observe the attachment of microorganisms and algae on the sample surface, and the ATP fluorescence method was used to quantitatively detect the biomass on the sample surface.

[0173] sample <![CDATA[Day 10 (g / m 2 )]]> <![CDATA[Day 30 (g / m 2 )]]> <![CDATA[Day 45 (g / m 2 )]]> <![CDATA[Day 60 (g / m 2 )]]> Example 1 0.2 1.5 2.6 4.8 Example 2 0.1 0.8 1.7 3.2 Example 3 0.3 1.2 2.2 3.9 Comparative Example 1 1.6 6.7 15.3 26.4 Comparative Example 2 0.9 3.8 7.4 13.5 Comparative Example 3 1.2 5.1 9.6 18.2 Comparative Example 4 0.5 2.3 5.2 9.8

[0174] Table 2

[0175] 3. Evaluation of coating mechanical properties and self-healing properties

[0176] Experimental conditions: Scratch test and erosion test were carried out at room temperature.

[0177] Experimental steps:

[0178] (1) Scratch test: Use a sharp blade to vertically scratch 10 scratches with a width of about 50 μm and a length of 1 cm on the coating surface, and then place it in a 60°C oven for 12 h; use an optical microscope to observe the scratch morphology changes before scratching, after scratching, and after self-repairing, and measure the scratch width;

[0179] (2) Erosion experiment: The coating sample was fixed on a rotating device and subjected to gravel erosion at a rotation speed of 1000 rpm for 2 h, and the weight loss rate of the coating was recorded; then it was allowed to stand for 72 h and weighed again to calculate the mass change before and after self-repair.

[0180] sample Scratch width change rate (%) Erosion weight loss rate (%) Weight loss rate after self-repair (%) Example 1 -85.6 1.8 0.5 Example 2 -62.3 2.2 1.1 Example 3 -78.1 1.5 0.3 Comparative Example 1 -21.4 6.7 5.8 Comparative Example 2 -55.7 3.2 2.4 Comparative Example 3 -48.2 4.5 3.7 Comparative Example 4 -32.9 2.6 2.2

[0181] Table 3

[0182] Results and discussion:

[0183] (1) According to the data in Table 1, it can be seen from the data of the hydrophobicity and self-cleaning performance of the coating surface that the water contact angles of the coating surfaces of Examples 1-3 are all above 155°, which are much higher than those of the comparative example, indicating that the fluorine-silicon modified epoxy resin significantly improves the hydrophobicity of the coating surface. At the same time, the amount of artificial stains remaining in Examples 1-3 is also much lower than that of the comparative example, proving that the micro-nanostructured coating synergistically constructed by fluorine-silicon modification and nano-composite fillers has excellent self-cleaning performance.

[0184] (2) According to the data in Table 2, from the evaluation results of the long-term antifouling performance of the coating, the amount of biological attachment in Examples 1-3 remained at a low level throughout the 60-day test period, while the comparative example showed a trend of substantial growth. This shows that the quaternary ammonium salt polymer capsules and organotin microspheres can form a long-lasting and stable antibacterial and anti-algae barrier on the coating surface through a controlled sustained release mechanism. In contrast, the rapid dissolution and loss of free quaternary ammonium salts and organotin molecules in Comparative Examples 2 and 3 caused their antifouling performance to decay rapidly.

[0185] (3) According to the data in Table 3, in terms of mechanical properties and self-healing properties of the coating, the scratch width of Examples 1-3 after the scratch test was reduced by an average of more than 70%, while the comparative example was only 20-50%, indicating that the dynamic bonding network and branched structure space effect constructed by the thiol-terminated hyperbranched molecules endowed the coating with significant self-healing ability. At the same time, the weight loss rate of Examples 1-3 in the erosion test and the remaining weight loss rate after self-healing were also significantly lower than those of the comparative example, which once again confirmed the synergistic effect of the self-healing element and the micro-nano composite structure in improving the mechanical strength, toughness and self-healing properties of the coating. Among them, Example 3 has the best comprehensive performance and is expected to become the preferred solution of the present invention.

[0186] Based on the above experimental data and mechanism analysis, the following conclusions can be drawn:

[0187] 1. The coating system of the present invention cleverly integrates multiple target synergistic mechanisms at different levels of surface chemistry (low surface energy fluorine-silicon modification), interface chemistry (quaternary ammonium salt capsules and organic tin polymer microspheres) and supramolecular chemistry (hyperbranched dynamic bonding network), and constructs an innovative solution to comprehensively improve the antifouling performance of ships through a multi-pronged approach.

[0188] 2. Different from the traditional single anti-fouling mechanism, the synergistic mechanism of the present invention not only prevents the adhesion and accumulation of pollutants on the coating surface from the source (superhydrophobic self-cleaning), but also inhibits the reproduction of microorganisms through controlled slow release by chemical means (quaternary ammonium salt capsules and organic tin polymer microspheres), as well as rapid self-repair from microscopic damage (hyperbranched dynamic chemical bonding), truly realizing long-term protection throughout the entire life cycle of the coating.

[0189] 3. More importantly, the multi-target synergistic mechanism of the present invention is not a simple superposition effect of "1+1>2", but through the carefully designed chemical components and structures, different functional units are mutually promoted and complement each other at the molecular, microscopic and macroscopic levels. For example, the hydrophobic coating surface is conducive to the uniform dispersion of sustained-release capsules and organotin polymer microspheres, and slows down hydrolysis degradation; while the nanocomposite filler not only enhances the strength of the matrix, but also provides more pin positioning points for the self-repairing element, promoting the construction of its dynamic bonding network.

[0190] 4. In addition, the synergistic mechanism of the present invention is also reflected in the compatibility of the antifouling element with other components. The introduced quaternary ammonium salt cationic surfactant is not only a highly effective antibacterial agent, but also can be used as an emulsifier to promote the dispersion of other components; while the hyperbranched macromolecules provide self-repairing function, they can also be used as a compatibilizer to improve the flexibility and impact resistance of the matrix. These "killing two birds with one stone" synergistic effects not only simplify the coating formula, but also help reduce production costs.

[0191] 5. Finally, it should be pointed out that the present invention fully embodies the bionics and green environmental protection concepts. The hydrophobic self-cleaning surface draws on the micro-nano structure of natural plants such as lotus leaves. The embedding and immobilization of organic tin polymer microspheres reduces the environmental release of tin. The quaternary ammonium salt and hyperbranched motif are also low-toxic and easily degradable organic substances. Therefore, the present invention is a new marine antifouling coating material with high efficiency, long-lasting effect and environmental friendliness.

[0192] In summary, the multi-target synergistic antifouling coating system of the present invention has achieved major breakthroughs in mechanism innovation, functional integration and environmental friendliness, and has demonstrated the great potential for the cross-integration of coating chemistry, materials science and biology. It is not only expected to fundamentally solve the fouling problem of marine vessels and other facilities, but also provides new ideas for the development of bionic intelligent materials and has broad application prospects.

[0193] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. An antifouling coating for marine vessels, characterized in that , comprising the following components in parts by weight: 40-60 parts of low surface energy fluorine-silicon modified epoxy resin; 10-30 parts of amino-modified nano titanium dioxide; 5-10 parts of amino-modified nano-silicon dioxide; 5-15 parts of quaternary ammonium salt polymer capsules; 5-10 parts of organotin polymer microspheres; 1-5 parts of thiol-terminated hyperbranched macromolecules; The preparation method of the low surface energy fluorine-silicon modified epoxy resin is as follows: 1-5 parts by weight of sodium dodecylbenzene sulfonate as an emulsifier is dissolved in 60-100 parts by weight of deionized water to obtain an emulsifier solution A; 1-3 parts by weight of hexadecanol as a stabilizer, 0.2-0.8 parts by weight of benzoyl peroxide as an initiator, 1-5 parts by weight of a vinyl silicone resin with a vinyl content of 0.01-0.06 mol%, 1-5 parts by weight of hexafluorobutyl methacrylate as a fluorine-containing monomer and 5-10 parts by weight of bisphenol A type epoxy resin E-44 are dissolved in 20-40 parts by weight of a styrene and A monomer solution B is obtained from a vinyl mixed monomer composed of butyl acrylate; the emulsifier solution A and the monomer solution B are mixed, stirred and dispersed at a speed of 200-400r / min for 20-40min; then ultrasonic emulsification is performed at a frequency of 15-40KHz, a power of 100-300W, and a time of 20-40min to obtain a droplet monomer emulsion; the droplet monomer emulsion is heated to 60-80°C, an inert gas is introduced and stirred and polymerized for 3-8h at a speed of 200-400r / min; after the polymerization is completed, the mixture is cooled to room temperature to obtain a low surface energy fluorine-silicon modified epoxy resin; The preparation method of the amino-modified nano titanium dioxide is: (1) Take 10 g of nano-titanium dioxide powder, add it into a beaker containing 100 mL of anhydrous ethanol, and disperse it by ultrasonic for 30 min to obtain a uniform titanium dioxide ethanol suspension; (2) Take 2 mL of γ-aminopropyltriethoxysilane and slowly add it dropwise into a three-necked flask containing 300 mL of deionized water. Stir and react at 50 °C for 2 h to obtain a uniform and transparent silane hydrolyzate. (3) Slowly add the titanium dioxide ethanol suspension in step (1) dropwise to the silane hydrolyzate in step (2), raise the temperature to 80°C, and reflux for 6 hours; (4) After the reaction is completed, the obtained white suspension is centrifuged, washed with deionized water 3 times, washed with anhydrous ethanol once, dried under vacuum at 60° C. for 4 h, and ground through a 120-mesh sieve to obtain amino-modified nano-titanium dioxide powder; The preparation method of the amino-modified nano-silica is: (1) Take 5 g of nano-silica aerogel and add it into a beaker containing 60 mL of anhydrous ethanol. Stir and disperse evenly, and ultrasonicate for 20 min to obtain a uniform and stable silica ethanol dispersion. (2) Take 3 mL of γ-aminopropyltriethoxysilane, dissolve it in 450 mL of deionized water, and stir it at room temperature for 30 min to obtain a silane hydrolyzate; (3) Under vigorous stirring, add the silicon dioxide ethanol dispersion in step (1) dropwise to the silane hydrolyzate in step (2), raise the temperature to 90°C after the addition is complete, and continue the reaction for 10 hours; (4) After the reaction is completed, the mixture is allowed to stand and cool to room temperature, filtered, the filter cake is washed with deionized water until it is neutral, vacuum dried at 70°C for 6 hours, and ground through a 200-mesh sieve to obtain amino-modified nano-silica powder; The preparation method of the quaternary ammonium salt polymer capsule is as follows: (1) dissolving 1-5 g of polymethyl methacrylate and 1-5 g of hexadecyltrimethylammonium bromide in 50-100 mL of water; (2) ultrasonically emulsifying the above solution to form an oil-in-water emulsion, with an ultrasonic frequency of 20-50 KHz, a power of 200-500 W, and a time of 10-30 min, and slowly dropping 0.5-2 g of anhydrous ethanol as an emulsifier during the emulsification process; (3) placing the emulsion in a 50-80° C. water bath and stirring for 2-6 h at a speed of 300-600 r / min to evaporate the water phase; (4) filtering the obtained precipitate and vacuum drying it to obtain polymethyl methacrylate capsules containing hexadecyltrimethylammonium bromide, with an average particle size of 5-20 μm; The preparation method of the organotin polymer microspheres is as follows: (1) 0.5-2mmol dibutyltin chloride and diphenyltin chloride are mixed in a molar ratio of 1:1 as template molecules, 4-8mmol methacrylic acid is used as a functional monomer, 5-20mmol trimethylolpropane trimethacrylate is used as a crosslinking agent, and 0.1-0.5mmol azobisisobutyronitrile is used as an initiator, and the mixture is dissolved in 50-100mL of an inert solvent formed by mixing dichloromethane and acetonitrile in a volume ratio of 3:1, and 0.01-0.05mmol 2,2'-azobis(2,4-dimethylvaleronitrile) is added as a molecular directing agent; (2) N2 is introduced to exclude oxygen for 20-40min, and then polymerization is carried out at 50-70°C for 20-30h; (3) the obtained block polymer is ground, passed through an 80-200 mesh sieve, and eluted with a methanol / acetic acid solution with a volume ratio of 9:1 to remove the template molecules; (4) vacuum drying the polymer particles to obtain organotin polymer microspheres with a particle size of 1-5 μm; The preparation method of the thiol-terminated hyperbranched macromolecule is as follows: (1) dissolving 0.1-0.5 g of trimethylolpropane tris(3-mercaptopropionate) as a trifunctional thiol monomer in 5-10 mL of N,N-dimethylformamide, adding 0.01-0.05 g of p-toluenesulfonic acid as an esterification catalyst, and stirring and deoxygenating for 20-40 min under a N2 atmosphere; (2) adding 0.05-0.3 g of 2-(acryloyloxy)-ethyl methacrylate as a difunctional acrylate monomer, and reacting at 40-60° C. for 20-30 h; (3) After the reaction is completed, add excess anhydrous ether, let stand to separate the layers, and take the lower organic phase; after removing the solvent by rotary evaporation, add dropwise to excess anhydrous ether to precipitate, and filter; dissolve the precipitate in dichloromethane, add dropwise to anhydrous ether again to precipitate, and repeat 2-4 times; vacuum dry the precipitate to obtain a terminal thiol hyperbranched polymer with a number average molecular weight of 5000-50000.

2. The antifouling coating for marine vessels according to claim 1, characterized in that The content of hexadecyltrimethylammonium bromide in the quaternary ammonium salt polymer capsule is 30-50% of the total weight of the capsule.

3. A method for preparing an antifouling coating for marine vessels according to any one of claims 1 to 2, characterized in that , including the following steps: 40-60 parts by weight of fluorine-silicon modified epoxy resin, 10-30 parts by weight of amino-modified nano titanium dioxide, 5-10 parts by weight of amino-modified nano silicon dioxide, 5-15 parts by weight of quaternary ammonium salt polymer capsules, 5-10 parts by weight of organic tin polymer microspheres and 1-5 parts by weight of thiol-terminated hyperbranched macromolecules are mixed, 60-100 parts of xylene are added, and the mixture is dispersed by ball milling for 2-6 hours to obtain a uniform coating; then 25-40 parts of a curing agent is added, wherein the curing agent is one or more of polyetheramine, diethylenetriamine, ethylenediamine, meta-xylene diamine, KH792 and KH550, and then the coating is applied to the surface of the hull by spraying or brushing, the coating thickness is controlled to be 50-200 μm, and the coating is cured for 24-48 hours at normal pressure and a temperature of 15-35° C.

Citation Information

Patent Citations

  • Organotin molecularly imprinted polymer microsphere, solid phase extraction column and use of solid phase extraction column

    CN106397655A

  • Long-lasting controlled-release ocean antifouling coating

    CN110358396A